Hydrogen Refueling Stations: A Review of the Technology Involved from Key Energy Consumption Processes to Related Energy Management Strategies - Rafael Pereira; Vitor Monteiro; Joao L. Afonso; Joni Teixeira (Energies)
Over the last few years, hydrogen has emerged as a promising solution for problems related to energy sources and pollution concerns. The integration of hydrogen in the transport sector is one of the possible various applications and involves the implementation of hydrogen refueling stations (HRSs). A key obstacle for HRS deployment, in addition to the need for well-developed technologies, is the economic factor since these infrastructures require high capital investments costs and are largely dependent on annual operating costs. In this study, we review hydrogen’s application as a fuel, summarizing the principal systems involved in HRS, from production to the final refueling stage. In addition, we also analyze the main equipment involved in the production, compression and storage processes of hydrogen. The current work also highlights the main refueling processes that impact energy consumption and the methodologies presented in the literature for energy management strategies in HRSs. With the aim of reducing energy costs due to processes that require high energy consumption, most energy management strategies are based on the use of renewable energy sources, in addition to the use of the power grid.